ANALISA DAN MANAJEMEN RISIKO DALAM PELAKSANAAN PEKERJAAN STRUKTUR - Haurissa, Ryan E; Iriyanto, Santje M; Iriyanti, Fatma M; Bakarbessy, Dominggus M; Pakiding, Leary M (DINAMIS, 2023)
The construction project of the Governor's Office in Papua used reinforced concrete with high-quality concrete strength, approximately 30 MPa or equivalent to K350 concrete. During the compressive strength testing, the concrete met the established standards. However, several structural elements exhibited damage during field observations, such as spalling, leakage, minor deterioration, and small cracks. A mixed-method research approach was employed to identify the causes of these issues. Questionnaires and interviews were utilized as quantitative methods with the assistance of SPSS software. A qualitative method using the Likert scale was also employed to analyze the risk level. The data analysis from the questionnaires and interviews revealed that the compaction work during the concrete casting process was not executed optimally, resulting in a level 3 risk (moderate risk, around 40%-60%). This risk could have significant implications for the project's quality if not addressed appropriately.